White elephant [videorecording (DVD)] - Johnson, Jesse V., 1971-; Martinez, Erik, 1978-; Rooker, Michael, 1955-; Willis, Bruce, 1955-; Kurylenko, Olga, 1979-; Malkovich, John (RLJE Films, 2022)
When an assassination attempt is witnessed by two cops, Gabriel Tancredi, an ex-marine turned mob enforcer, is ordered by his ruthless mob boss to eliminate any and all threats. With an eager underling out to prove himself, rival gangs making moves and a rising body count, every step Tancredi makes threatens lives... including his own.